2001
DOI: 10.1177/136346001004004002
|View full text |Cite
|
Sign up to set email alerts
|

Anal Intercourse and Power in Sex Between Men

Abstract: Anal intercourse between men is discussed using various texts, primarily interview narratives. The focus is upon the way men talk about and experience anal intercourse as a relation of power between men. Drawing upon the work of Foucault, a distinction is made between power as domination and power as negotiated between people. The latter opens up the possibility of intimacy and mutual pleasure within fantasies of domination and submission. Some of the men's narratives embraced the idea that the anally insertiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 5 publications
4
73
0
Order By: Relevance
“…As Kippax and Smith (2001) observe, for a man with a masculine subjectivity to be a bottom might threaten their masculine identity. The participants in this study suggested that some bottoms seek masculine capital in other domains-for example, by exercising to achieve muscularity-in an attempt to overcome the feminine connotations of being a bottom, and thus to ameliorate this threat to their masculinity.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…As Kippax and Smith (2001) observe, for a man with a masculine subjectivity to be a bottom might threaten their masculine identity. The participants in this study suggested that some bottoms seek masculine capital in other domains-for example, by exercising to achieve muscularity-in an attempt to overcome the feminine connotations of being a bottom, and thus to ameliorate this threat to their masculinity.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…The significance of sexual role in anal intercourse for gay men has been the subject of previous research. Kippax and Smith (2001), for example, found that most gay men described gay anal intercourse in terms of masculine-feminine and dominance-submission binaries, associating the insertive role with masculine dominance and the receptive role with feminine submission. However, as in the present study, some of the gay men in Kippax and Smith's (2001) study also contested these binary descriptions, constructing bottoms as powerful, and having "strength in submission" (p. 430).…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research shows that the use of labels of top or bottom also relate to other intricate dynamics of power and erotics and that such labels do not easily demarcate who is passive or powerless in the relationship (Hoppe 2011;Kippax and Smith 2001). Foucault's (1993) notion of the productive nature of discourse is useful to thinking about the place of power here.…”
Section: Top/bottom Constructs Amongst Gay Men: Implications For Sexumentioning
confidence: 99%
“…Constructs of sexuality in terms of being a 'top' or a 'bottom' have been explored by researchers interested in the sexual identification and practice of gay men, and attest to the complexities of identification that language and labelling practice imply in general (GrundyBowers, Hardy and McKeown 2015;Johns et al 2012;Kippax and Smith 2001;Matebeni and Msibi 2015;McGill and Collins 2014a;McGill and Collins 2014b;.…”
Section: Top/bottom Constructs Amongst Gay Men: Implications For Sexumentioning
confidence: 99%